CHANGES IN GENDER IDEOLOGY IN DOMESTIC CHORES AMONG PROFESSIONAL MALAY MUSLIM MEN IN DUAL-CAREER FAMILIES: A STUDY IN KUALA LUMPUR AND SELANGOR - Zuraini Jamil @ Osman; Tan Bee Piang; Noor Banu Mahadir, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This study focuses on professional Malay Muslim men in dual-career families in Kuala Lumpur and Selangor. I conducted semi-structured, in-depth interview with 10 Malay Muslim men in dual-career families to gather the data. Drawing upon interviews with the respondents, this study is able to highlight their understanding of the division of labour at home and how this impacts upon and influences their views about the roles and responsibilities of men and women in relation to the division of labour at home and the division of categories of housework by gender. All of the respondents agreed that household tasks should be carried out together with their wives, but they had different views about the division of household chores in regard to what men and women should do. This study also found that the respondents did not face condemnation and derision from their extended family members or friends when they help their wives with the household tasks. It is generally accepted that this study shows that the gender ideology has slightly changed and negotiate. In practice, however, they stated that the household chores still are seen as under women’s responsibility. Although this study reveals the acceptance of changes to the traditional gender role ideology, the traditional perspective and understanding in terms of the domestic chores continue to exist and are well sustained. While Malaysia’s drive for modernization has improved Malay society, it has not radically transformed the patriarchal order as the traditional patriarchal system that prescribes specific gendered expectations for both women and men in private spheres still ingrained in their culture.